Relationship between Cholesterol Levels and Ca 15-3 Tumor Markers in Patients with Carcinoma Mammae - Faylori, Adelia Yusnita; Pauzi, Iswari; Fihiruddin (Universitas Pendidikan Mandalika, 2025)
Breast cancer is the most common malignancy among women worldwide and remains a major cause of cancer-related mortality in Indonesia. Various risk factors, including hormonal, genetic, lifestyle, and metabolic factors, such as elevated cholesterol levels, have been associated with the development and progression of breast cancer. Cholesterol plays a crucial role in cell membrane formation and hormone synthesis, and recent studies have suggested its potential role in tumor growth and metastasis, particularly through the modulation of estrogen receptors and inflammatory pathways. CA 15-3 is a tumor marker widely used for monitoring breast cancer progression and recurrence. However, the correlation between cholesterol levels and CA 15-3 remains underexplored. The research objective is to determine the correlation between total cholesterol levels and the breast cancer tumor marker CA 15-3 in patients diagnosed with breast carcinoma at the Regional General Hospital of West Nusa Tenggara Province (RSUDP NTB). A cross-sectional analytic observational study was conducted using secondary data from the medical records of 33 breast carcinoma patients collected between January to November 2024. Cholesterol and CA 15-3 levels were analyzed using standard laboratory procedures. Data distribution was tested using the Kolmogorov-Smirnov test, and Pearson correlation analysis was applied to evaluate the relationship between cholesterol levels and CA 15-3. Showed that the mean cholesterol level was 214.24 mg/dL, and the mean CA 15-3 level was 41.55 U/mL, both exceeding normal reference values. Pearson correlation analysis demonstrated a very strong and statistically significant positive correlation between total cholesterol and CA 15-3 levels (r = 0.940, p < 0.001), indicating that higher cholesterol levels are associated with increased CA 15-3 concentrations. The study found a significant correlation between cholesterol levels and CA 15-3 in breast carcinoma patients, suggesting that cholesterol may influence tumor activity. Routine monitoring of cholesterol levels may be valuable in the clinical management of breast cancer, especially in assessing disease progression.